(untitled) (Malaysian Journal of Learning and Instruction, 2017)
Purpose – This study investigated rural English teachers’ perceptions of factors which influence the literacy development of young learners in rural school settings. This investigation led to a further enquiry on the dimensions of an affective literacy framework to support the English learning of rural young learners. Methodology – The study employed a qualitative approach to provide a holistic view of the phenomena being studied. Two English optionist teachers and two non-optionist teachers volunteered to participate in the study. The first investigation was based on audiotaped interview sessions with the teachers, and the second enquiry was grounded in video-taped class observations. The raw data from these instruments were used for qualitative content analysis, which resulted in the proposed Affective Literacy Framework for Rural Young Learners (ALFRYL). Findings – The analysis of interviews indicated that the teachers acknowledged the critical need for creating effective and interesting activities that can engage young learners cognitively and affectively, while arguing that their training background and learning experiences primarily influenced their pedagogical approaches. Classroom observations noted that the optionist teachers were confident in their pedagogical delivery. Based on the analysis of the affective teaching foci illustrated by the teachers in the classroom, six components of an affective literacy framework were identified as a tool to support affective literacy development among rural young learners: learner diversity, engaging pedagogy, meta-cognitive assessment, emotional management, pedagogical resources and positive interaction. Significance – Providing pedagogical examples of how teachers frame the task of teaching English in rural areas, this study illustrates the realities of their struggle, which teachers in similar situations may face in helping pupils learn English effectively. Positive affective literacy environments would provide opportunities for young learners not only to make meaning but also to reach new language materials and express themselves in new ways. The dimensions that constitute the affective literacy framework makes available an initial reference for teachers to stimulate pupils’ learning in challenging contexts where English is used minimally.